PENGARUH CITRA MEREK, PERCEIVED VALUE, DAN PENGALAMAN PELANGGAN TERHADAP LOYALITAS PENGGUNA IPHONE - Pradida, Debbi Rangga; Suryadi, Nanang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to identify the effects of brand image, perceived value, and customer experience on the loyalty of iPhone users in Malang city. This is an explanatory research because it explains causal relationships between variables through hypothesis testing. The sample was selected using non-probability sampling method and purposive sampling technique, resulting in 150 respondents. The data analysis includes descriptive analysis, classical assumption test, multiple linear regression, and hypothesis testing. This study finds that brand image, perceived value and customer experience positively and significantly influence the loyalty of iPhone users in Malang city. This study also finds that iPhone is a smartphone brand with technological superiority and that the values contained in iPhone meet the customers expectation prior to the purchase of the product. Furthermore, the product influences customer loyalty. The experience of using iPhone ensures that users will choose iPhone as their smartphones in the future. This means that the loyalty of iPhone users in Malang city is affected by brand image, perceived value, and customer experience.